2005
DOI: 10.1007/s00418-005-0055-3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired formation of desmosomal junctions in ADPKD epithelia

Abstract: Mutations in polycystin-1 (PC-1) are responsible for autosomal dominant polycystic kidney disease (ADPKD), characterized by formation of fluid-filled tubular cysts. The PC-1 is a multifunctional protein essential for tubular differentiation and maturation found in desmosomal junctions of epithelial cells where its primary function is to mediate cell-cell adhesion. To address the impact of mutated PC-1 on intercellular adhesion, we have analyzed the structure/function of desmosomal junctions in primary cells de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…[14][15][16] Importantly, disruption of desmosomal and adherens cell-cell junctions were detected in cystic ADPKD epithelia, suggesting that mutations in polycystin-1 lead to perturbation of intercellular adhesion complexes and cystogenesis. 17,18 In addition, polycystin-1 was found in focal adhesion complexes suggesting its role in cell-matrix adhesion. 19,20 These data clearly suggest that mutation in polycystin-1 results in the disruption of cell-cell/matrix adhesion, which, in turn leads to increased proliferation, de-differentiation and cystic transformation.…”
Section: Polycystins Function In Multiple Subcellular Domainsmentioning
confidence: 99%
“…[14][15][16] Importantly, disruption of desmosomal and adherens cell-cell junctions were detected in cystic ADPKD epithelia, suggesting that mutations in polycystin-1 lead to perturbation of intercellular adhesion complexes and cystogenesis. 17,18 In addition, polycystin-1 was found in focal adhesion complexes suggesting its role in cell-matrix adhesion. 19,20 These data clearly suggest that mutation in polycystin-1 results in the disruption of cell-cell/matrix adhesion, which, in turn leads to increased proliferation, de-differentiation and cystic transformation.…”
Section: Polycystins Function In Multiple Subcellular Domainsmentioning
confidence: 99%
“…In MDCK cells, we found that PC1 was 1411 PC1 and junction assembly coimmunoprecipitate with E-cadherin and the catenins in human pancreatic adenocarcinoma cells (Huan and van Adelsberg, 1999). In human cystic cells, the absence of surface PC1 is associated with concomitant loss of surface E-cadherin expression and its replacement by N-cadherin (Streets et al, 2003;Roitbak et al, 2004;Russo et al, 2005). A putative role for PC1 in desmosome function has also been postulated because of its immunolocalisation to desmosomal junctions, the mislocalisation of desmosome junction proteins in cystic cells and the reported interaction of the PC1 C-terminus with intermediate filaments (Scheffers et al, 2000;Xu et al, 2001;Russo et al, 2005;Silberberg et al, 2005).…”
Section: Introductionmentioning
confidence: 91%
“…In ADPKD cysts, these desmosomal elements are severely disoriented [42] . Finally, cytoskeletal proteins such as actinbinding proteins, cardiac troponin and tropomysin have been directly associated with PC2 channel activity upon stimulation by osmotic or hydrostatic pressure [43,44] .…”
Section: Referencesmentioning
confidence: 99%